Separation of black oat seeds from wheat seeds - Possenti, Jean Carlo; Villela, Francisco Amaral; Zimmer, Gilberto Jaime (Pesquisa Agropecuaria Brasileira, 1997)
A study was made in Pelotas, RS, Brazil, of the separation of black oat seeds from wheat seeds, determining the capability and efficiency of an air-screen cleaner (ASC) and gravity table (GT) in this operation. Seed packs of the wheat cultivar EMBRAPA-16 and seeds of black oat, common cultivar, were used and in the processing, the ASC and the GT. In the ASC, four screens were utilized: 1.9 x 20; 2.0 x 20; 2.1 x 20 and 2.2 x 20 mm, with oblong bores in the position of the fourth screen and three contamination levels: 5; 10 and 15 black oat seeds for each 100 g of wheat seeds. The results led to the conclusion that: a) it is possible to separate black oat seeds from wheat seeds during processing; b) the use of the 2.1 x 20 screen in the ASC, independently of the contamination level, allows separating black oat seeds from wheat seeds, putting the pack of seeds within the minimum standards required for marketing; c) the utilization of the ASC cleaner and screens followed by the GT, fully retains the black oat seeds from packs of wheat seeds; d) the initial contamination level does not affect the loss in the sequence ASC and screens and gravity table.